Effect of Doping on the Thermal Decomposition of Zinc Oxalate - Suryanarayanan, M.P.; Radhakrishnan Nair, T.D. (Asian Journal of Chemistry, 2010)
The influence of cation doping on the thermal decomposition of zinc oxalate was studied. Dopants such as Co2+ and Ni2+ have been found to decrease Ti, E, Z and ΔS*. The phenomenon may be linked to the ability of Co and Ni to form carbonyls during pyrolysis. The effect of the dopants on mechanism of decomposition was also studied. The presence of dopants was detected by inductively coupled plasma atomic absorption spectrum.